Exploring the Association between Diabetes Mellitus, Obesity, and Recurrent Stroke Events: a Cross-sectional Study - Marlina, Marlina; Sari, Maulida; Amni, Rahmalia (Global Medical & Health Communication (GMHC), 2024)
Stroke is the most significant cause of death and cause of disability in the world because it causes neurological deficits in sufferers, such as muscle paralysis, swallowing weakness, communication damage, and vision disorders to cause death. Stroke can be recurrent and have a severe impact compared to the initial attack. The purpose of this study was to explore the association between diabetes mellitus, obesity, and the incidence of recurrent strokes in post-stroke patients at a regional general hospital in Aceh province. It is a cross-sectional study carried out from 3–12 August 2022. The sampling technique used in this study was a purposive sampling of 154 patients. The instruments used were questionnaires of patient demographic characteristics, data analysis using chi-square assays, and logistic regression. The results showed that there was no association between diabetes mellitus (p>0.05) and obesity (p>0.05) with the incidence of recurrent strokes. One of the preventive measures for the occurrence of recurrent strokes is to provide education about the prevention of recurrent strokes related to diabetes mellitus and obesity, one of which is a healthy lifestyle. In conclusion, there is no relationship between diabetes mellitus, obesity, and the incidence of recurrent strokes in post-stroke patients at a regional general hospital in Aceh province.